ANALYSIS OF THE ECONOMIC DEVELOPMENT OF THE TRANSPORT SECTOR IN OUR COUNTRY AND THE FORMATION OF DIGITAL MARKETING IN THIS FIELD - Raxmatullayeva , Sadokat (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes the economic development of the transport sector in our country and the state of formation of digital marketing in it. Also, conclusions are drawn from the study of the economic development of the transport sector in our country.